Identification and Evaluation of New Immunoregulatory Genes in Mesenchymal Stromal Cells of Different Origins: Comparison of Normal and Inflammatory Conditions - Fayyad-Kazan, Mohammad (Med Sci Monit Basic Res, 2017)
BACKGROUND: Mesenchymal stromal cells (MSCs) possess potent immunomodulatory properties that increase their value as a cell-based therapeutic tool for managing various immune-based disorders. Over the past years, accumulated results from trials using MSCs-based therapy have shown substantial contradictions. Although the reasons underlying these discrepancies are still not completely understood, it is well known that the immunomodulatory activities mediated by distinct MSCs differ in a manner dependent on their tissue origin and adequate response to inflammation priming. Thus, characterization of new molecular pathway(s) through which distinct MSC populations can exert their immunomodulatory effects, particularly during inflammation, will undoubtedly enhance their therapeutic potential. MATERIAL/METHODS: After confirming their compliance with ISCT criteria, quantitative real time-PCR (qRT-PCR) was used to screen new immunoregulatory genes in MSCs, derived from adipose tissue, foreskin, Wharton’s jelly or the bone-marrow, after being cultivated under normal and inflammatory conditions. RESULTS: FGL2, GAL, SEMA4D, SEMA7A, and IDO1 genes appeared to be differentially transcribed in the different MSC populations. Moreover, these genes were not similarly modulated following MSCs-exposure to inflammatory signals. CONCLUSIONS: Our observations suggest that these identified immunoregulatory genes may be considered as potential candidates to be targeted in order to enhance the immunomodulatory properties of MSCs towards more efficient clinical use.